(untitled) (London Journal of Research In Science: Natural and Formal, 2023)
3-D seismic attribute analysis and reservoir pore-fill characterization was carried out in an X-field in the Niger Delta petroleum province Nigeria. The main objective of the study was to establish a relationship between selected seismic attributes and reservoir fluid types in the X-field, and then erect a model for reservoir pore-fill interpretation using the selected seismic attributes. To achieve the above objective, data which include: 3-D seismic sections, seismic attribute maps (amplitude, frequency, phase and polarity) of a selected horizon (M10) and digital well logs were compiled, and an integrated analysis finally performed on the data set. It was observed that seismic reflection polarity values above 4,574 were seen to be indicative of good reservoir sands while values less than -3,520 were seen to represent shale with good sealing capacity. Amplitudes less than 13,480 signified an unfavourable event while values between 13,840 and 17,789 were indicative of oil, and all true amplitude greater than 19,764 represented gas. Frequencies between 18.6 – 17.9 Hz were seen to represent oil and those below 17.0 Hz corresponded to gas. Finally, the reservoir pore-fills in the chosen horizon (M10) was interpreted to be gas around well (7) and the western limits of the horizon, and oil around well (4). In conclusion, the above results were integrated to erect a pre drilling guide for reservoir pore-fill interpretation from seismic attribute analysis of 3D seismic data volume in the X -field.